2012
DOI: 10.1093/molehr/gas017
|View full text |Cite
|
Sign up to set email alerts
|

Global alteration in gene expression profiles of deciduas from women with idiopathic recurrent pregnancy loss

Abstract: Recurrent pregnancy loss (RPL) occurs in ∼5% of women. However, the etiology is still poorly understood. Defects in decidualization of the endometrium during early pregnancy contribute to several pregnancy complications, such as pre-eclampsia and intrauterine growth restriction (IUGR), and are believed to be important in the pathogenesis of idiopathic RPL. We performed microarray analysis to identify gene expression alterations in the deciduas of idiopathic RPL patients. Control patients had one antecedent ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 76 publications
(60 citation statements)
references
References 47 publications
2
56
0
2
Order By: Relevance
“…Similar results were observed in human first-trimester DSCs in which the Sphk deficiency dramatically increased the secretion of CXCL1, IL-8, and IL-6. Recent microarray analysis demonstrated for the first time that genes in the IL-8 pathway were up-regulated in deciduas from patients with idiopathic RPL compared with those from control miscarriage patients with aneuploid embryonic demises who had experienced at least one term delivery and no previous miscarriages (50). Taken together, these results indicate that Sphk-deficient mice may be a useful animal model for gaining a comprehensive understanding of the mechanisms underlying pregnancy loss and assist in the development of treatment for human idiopathic RPL.…”
Section: Sphk2mentioning
confidence: 99%
“…Similar results were observed in human first-trimester DSCs in which the Sphk deficiency dramatically increased the secretion of CXCL1, IL-8, and IL-6. Recent microarray analysis demonstrated for the first time that genes in the IL-8 pathway were up-regulated in deciduas from patients with idiopathic RPL compared with those from control miscarriage patients with aneuploid embryonic demises who had experienced at least one term delivery and no previous miscarriages (50). Taken together, these results indicate that Sphk-deficient mice may be a useful animal model for gaining a comprehensive understanding of the mechanisms underlying pregnancy loss and assist in the development of treatment for human idiopathic RPL.…”
Section: Sphk2mentioning
confidence: 99%
“…The MMP12 is a key mediator of elastolysis and contributes to the remodeling of spiral arteries. Expression of the MMP12 gene was found to be upregulated in deciduas of women with IRSA compared to controls [12]. The A allele of the MMP12 -82 A/G SNP enhances the binding of the transcription factor activator protein 1, increasing promoter activity [45].…”
Section: Discussionmentioning
confidence: 95%
“…During the secretory phase, including the implantation window and decidual transformation, the expression profiles of endometrial genes are changed considerably compared to proliferative phase [5][6][7][8]. It has been suggested that abnormalities in gene expression during the secretory phase may lead to inappropriate endometrial development and, consequently, various reproductive disorders, including recurrent spontaneous abortion [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has not been studied greatly, however in patients with euploid miscarriages, upregulation of the proinflammatory IL-8 in the decidua has been seen [123].…”
Section: Il-8mentioning
confidence: 99%